Can agricultural subsidies reduce gendered productivity gaps? Panel data evidence from Zambia - Ngoma, Hambulo (Indaba Agricultural Policy Research Institute, Zambia, 2018)
Presented by Hambulo Ngoma (IAPRI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.